Comparison of the in vitro Anti-Inflammatory Effect of Cannabidiol to Dexamethasone - Wang Y; Wang X; Yang Y; Quan Q; Huo T; Yang S; Ju R; An Q (Dove Medical Press, 2022)
Yiming Wang,1- 3 Xue Wang,1- 3 Yang Yang,1- 3 Qianghua Quan,1- 3 Tong Huo,1- 3 Simin Yang,4 Ruijun Ju,4 Quan An1- 3,5 1Research and Development Department, Yunnan Baiyao Group Health Products Co, Ltd, Kunming, People's Republic of China; 2East Asia Skin Health Research Center, Beijing, People's Republic of China; 3Research and Development Department, REAL DermaSci & Biotech Co, Ltd, Beijing, People's Republic of China; 4Beijing Key Laboratory of Enze Biomass Fine Chemicals, Department of Pharmaceutical Engineering, Beijing Institute of Petrochemical Technology, Beijing, People's Republic of China; 5Research and Development Department, Yunnan Baiyao Group Shanghai Science & Technology Co, Ltd, Shanghai, People's Republic of ChinaCorrespondence: Quan An, Yunnan Baiyao Group Health Products Co, Ltd, 3686 Yunnan Baiyao Street Chenggong District, Kunming, 650500, People's Republic of China, Tel +86-13529091004, Email ynbyanquan@sina.comBackground: Cannabidiol (CBD) is a non-psychoactive phytocannabinoid constituent of Cannabis sativa with pain-relieving and anti-inflammatory properties. With the emphasis on natural ingredients in cosmetics, CBD has become a new cosmetic ingredient due to its ability to alleviate inflammation. However, in-depth studies that directly compare the effective mechanism and the therapeutic potential of CBD are still needed.Purpose: The aim of the present study was to investigate the anti-inflammatory effect of CBD in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages and compare it to dexamethasone (DEX).Methods: RAW264.7 macrophages in the logarithmic growth phase were incubated in the presence or absence of LPS. After that, the production of nitric oxide (NO), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) were measured. A luciferase reporter assay for nuclear factor kappa B (NF-κB) was performed, and the phosphorylation levels of the mitogen-activated protein kinase (MAPK) and NF-κB signaling pathways were measured.Results: The present study indicated that CBD had a similar anti-inflammatory effect to DEX by attenuating the LPS-induced production of NO, IL-6, and TNF-α. However, only CBD attenuated JNK phosphorylation levels, and only DEX attenuated IKK phosphorylation levels.Conclusion: These results suggested that CBD and DEX exhibit similar anti-inflammatory effects on LPS-induced RAW264.7 macrophages mainly through suppressing the MAPK and NF-κB signaling pathways, but with different intracellular mechanisms. These findings suggested that CBD may be considered a natural anti-inflammatory agent for protecting skin from immune disorders.Graphical Abstract: Keywords: cannabidiol, dexamethasone, LPS, RAW264.7, anti-inflammation